2015
DOI: 10.1080/17451000.2015.1047381
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the genetic diversity of the mangrove oysterCrassostrea rhizophorae(Bivalvia, Ostreidae) by microsatellite markers in southeastern Brazil

Abstract: Oysters of the genus Crassostrea are an economically important resource occurring along the Brazilian coast, mainly in estuarine regions. Inter-and intra-population genetic diversity is essential for monitoring long-term genetic changes and for sustainable use of this bivalve by coastal fishing communities. Microsatellite markers were used to evaluate the genetic diversity of natural populations of the mangrove oyster Crassostrea rhizophorae in southeastern Brazil. Samples of 150 oysters from four areas were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Five out of eleven microsatellite loci finally selected in this study showed significant HWE deviations due to heterozygote deficiency commonly detected in aquatic organisms (An et al 2013;Galvão and Hilsdorf 2015;Gonzalez et al 2012;Valles-Jimenez et al 2004;Yu and Li 2007). Many factors could cause these deficit deviations, such as biological factors (inbreeding, Wahlund effect, and gene flow), technical factors (null alleles, technical artifacts, and small sampling size) (Valles-Jimenez et al 2004).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Five out of eleven microsatellite loci finally selected in this study showed significant HWE deviations due to heterozygote deficiency commonly detected in aquatic organisms (An et al 2013;Galvão and Hilsdorf 2015;Gonzalez et al 2012;Valles-Jimenez et al 2004;Yu and Li 2007). Many factors could cause these deficit deviations, such as biological factors (inbreeding, Wahlund effect, and gene flow), technical factors (null alleles, technical artifacts, and small sampling size) (Valles-Jimenez et al 2004).…”
Section: Discussionmentioning
confidence: 93%
“…Subsequently, the multiplex products are analyzed using gel capillary electrophoresis and then genotyped. The multiplex PCR assay using microsatellite markers, a time and cost-effective technique, has become a powerful tool to study the genetic diversity and structure of natural populations of bivalves including oysters (An et al 2013;Galvão and Hilsdorf 2015), mussels (Wenne et al 2022), clams (Hargrove et al 2015), and scallops (Morvezen et al 2015). However, there have been limited studies on population genetics of M. unguiculatus.…”
Section: Introductionmentioning
confidence: 99%
“…The Fraser River system consisted of five white sturgeon ( Acipenser transmontanus ) management units, two of which were listed as endangered populations under Canada’s Species at Risk Act, which were verified with microsatellite markers [ 245 ]. Microsatellites were applied in the assessment of using barriers for the conservation of native salmonid populations threatened by non-native migratory fish invasions [ 246 ], analysis of population genetic structure of endangered freshwater pearl mussel ( Margaritifera margaritifera L.) in Europe, elaboration of the recommendation concerning conservation units [ 247 ] and study of population genetics of the exploited oyster, Crassostrea rhizophorae , in Brazil [ 248 ].…”
Section: Conservation Geneticsmentioning
confidence: 99%
“…Subsequently, the multiplex products are analyzed using gel capillary electrophoresis and then genotyped. The multiplex PCR assay using microsatellite DNA markers, a time and cost-effective technique, has become a powerful tool to study the genetic diversity and structure of natural populations of bivalves including oysters (An et al 2013, Galvão andHilsdorf 2015), mussels (Wenne et al 2022), clams (Hargrove et al 2015), and scallops (Morvezen et al 2015).…”
Section: Introductionmentioning
confidence: 99%